2018
DOI: 10.1039/c8sc01580e
|View full text |Cite
|
Sign up to set email alerts
|

Preparative microdroplet synthesis of carboxylic acids from aerobic oxidation of aldehydes

Abstract: Preparative synthesis of carboxylic acids from the aerobic oxidation of aldehydes in microdroplets with moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…55 This acceleration presumably arises as the microdroplet evaporates, a process that leads to high concentrations of reagents in conned spaces. Additional factors such as change in pH, 27,28 droplet size, 28,29 reagent concentration, 28,34,46 solvent system, 17,30 and droplet temperature, 30,31 may also inuence these reactions.…”
Section: Rate Acceleration Relative To Bulk-phase Control Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 This acceleration presumably arises as the microdroplet evaporates, a process that leads to high concentrations of reagents in conned spaces. Additional factors such as change in pH, 27,28 droplet size, 28,29 reagent concentration, 28,34,46 solvent system, 17,30 and droplet temperature, 30,31 may also inuence these reactions.…”
Section: Rate Acceleration Relative To Bulk-phase Control Reactionsmentioning
confidence: 99%
“…Recently, the groups of Cooks, [17][18][19][20][21][22][23][24][25][26] Zare, [27][28][29][30][31][32][33][34][35][36][37][38][39] and others [40][41][42][43][44][45][46] have reported the acceleration of reactions in microdroplet environments during the process of electrospraying reagents into a mass spectrometer. 32 Intrigued by the possibility of faster rates for multicomponent reactions, we explored the use of microdroplets as a means of enabling a rapid Biginelli reaction (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Some factors, like size, with or without high voltage, solvent, and lasting reaction time of the microdroplet will have a direct effect on the high yields. 40 Recently, there have some technology explored for increasing the yield of the product and scaling-up the microdroplet reaction. 21,38,[40][41][42] Heated ultrasonic nebulization (HUN) has been used successfully for this purpose in our group.…”
Section: Introductionmentioning
confidence: 99%
“…40 Recently, there have some technology explored for increasing the yield of the product and scaling-up the microdroplet reaction. 21,38,[40][41][42] Heated ultrasonic nebulization (HUN) has been used successfully for this purpose in our group. 43 We report here the use of ultrasonic nebulization to make a scaled-up preparation the catalytic Au-(His) 2 complex.…”
Section: Introductionmentioning
confidence: 99%
“…† As the temperature was increased from 30 C to 50 C, the average droplet size decreased from 6.9 mm to 5.4 mm, which is closer to the microdroplet size (2-3 mm) in ESI. Previous reports 39,55,56 have indicated that the droplet size has a large effect on the reaction rate in microdroplets; thus we speculate that the increased reaction rate in HUN at higher temperature is caused by the smaller droplet size. The following three reactions were also conducted at 50 C. The reaction in the nebulization cell is accelerated by the continuously atomized microdroplets from the reactant solution.…”
Section: Resultsmentioning
confidence: 55%